PENINGKATAN KETERAMPILAN GERAK TARI MELALUI METODE DRILL PADA SISWA KELAS VII B KABUPATEN BENGKAYANG - Puja, Kristianus; fretisari, Imma; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to desecrate students’ dance movement skills improvement by implementing drilling method in dance subject of Class VII B of Junior High School 1 of Bengkayang District. The problems faced by the students were the lack of dancing skills and practices, this making them feel nervous, stiff, and unconfident when being asked to do dance moves. This was due to habits in learning art and culture in class, especially dance subject, the teachers dominantly explain the material theoretically instead of practically. This study was a qualitative descriptive research in form of a classroom action research by implementing drilling method in the learning. This study was conducted in two cycles in the form of practical tests for students in which at the end of each cycle the students were assigned to practically present the dance performance. The findings showed that students’ practical dancing skills have improved, that is, the students were able to dance easily and flexibly. Hence, the students were more fluent in practicing the dance movements. The skills from cycle 1 to cycle 2 have improved from the mean scores 69,03 to 85,43. Hence, drilling method was effective in improving students’ dancing practice skills. Keywords: Drilling method, Dance movement , Skill improvement.